The Formation of Posture of Pupils as an Actual Problem - Alla Aleshina (Lesya Ukrainka Volyn National University, 2015)
The process of forming of carriage of children is analyzed. Anatomic and physiology factors which influence on the process of forming of correct carriage are determined. The biomechanics aspects of forming of carriage and factors which have an influence on it are studied. Basic principles and facilities of formings of carriage, which assist to harmonious development of personality of schoolboys are analysed. The substantive provisions of creation of complexes of physical exercises directed on forming of correct carriage are studied. The basic principles of forming of correct carriage are determined and the flow-chart of methods of its forming is worked out, which contains such constituents: forming of knowledge about a carriage, forming of motivation to the prophylaxis of carriage, forming of theoretical knowledge about the methods of prophylaxis of carriage, and also practical skills of realization of the offered complexes of physical exercises and control and analysis of results.